Empoderamento psicológico em enfermagem – tradução, adaptação e validação do "Psychological Empowerment Instrument" - Teixeira, Abílio Cardoso (2018)
BACKGROUND: Professional Empowerment in Nursing has a positive impact on the nurse, the patient, the Health institutions and the subject of nursing itself and it is, therefore, of the utmost importance. AIM: The need for this study came from the absence of an instrument capable of measuring Empowerment validated for the Portuguese population (from a psychological perspective). We aimed to translate, adapt and validate the "Psychological Empowerment Instrument". METHODS: In a methodological study, through translation and back-translation, while using a stratified probability sample formed by nurses in a general hospital in Oporto, Portugal. RESULTS: Four factors were identified through the factor analysis coinciding with those identified by Spreitzer (1995). These factors explain 73,504% of the total variance of the scale and isolated they explain 24,459 (Meaning), 18,780 (Impact), 15,470 (Self-determination) and 15,028 (Competence). The reliability of the scale was estimated using Cronbach's alpha coefficient, with a total of 0,824 (the value of the different dimensions ranging from 0,688 to 0,868), and so we considered that this scale had internal consistency. We also verified a statistically significant correlation between different dimensions, varying Pearson’s correlation coefficients between 0.173 and 0.594. CONCLUSION: Therefore, we believe to have obtained a version of "Psychological Empowerment Instrument" valid for the sample under study.